ANALISIS PENERAPAN TOTAL QUALITY MANAGEMENT (TQM) UNTUK MENINGKATKAN KINERJA MANAJERIAL PADA PT. Arina Hijab Ganding - Junaidi Efendi; Moh Hanafi; Nurul Mustofa; Moh Andi Firmansyah (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze the implementation of Total Quality Management (TQM) in improving managerial performance at PT. Arina. TQM is a management approach that emphasizes continuous improvement, the involvement of all organizational members, and a focus on customer satisfaction to achieve a company's competitive advantage. The research method used was qualitative, with primary data sources obtained through observation, interviews, and documentation. The collected data were analyzed based on the TQM elements implemented within the company. The results indicate that PT. Arina has implemented most of the TQM elements, including customer focus, quality obsession, a scientific approach, long-term commitment, teamwork, continuous system improvement, controlled freedom, unity of purpose, and employee involvement and empowerment. The implementation of these elements has had a positive impact on improving managerial performance and the company's operational effectiveness. However, education and training have not been optimally implemented because the company has not provided a structured and ongoing training program for employees. Therefore, improving education and training aspects is necessary to ensure more effective TQM implementation and optimally support the achievement of company goals.